Defining Genome-Wide Expression and Phenotypic Contextual Cues in Macrophages Generated by Granulocyte/Macrophage Colony-Stimulating Factor, Macrophage Colony-Stimulating Factor, and Heat-Killed Mycobacteria - Bazzi, Samer; El-Darzi, Emale; McDowell, Tina; Modjtahedi, Helmout; Mudan, Satvinder; Achkar, Marcel; Akle, Charles; Kadara, Humam; Bahr, Georges M. (Frontiers in Immunology, 2017)
Heat-killed (HK) Mycobacterium obuense (M. obuense; NCTC13365) is currently being evaluated in the clinic as an immunotherapeutic agent for cancer treatment. Yet, the molecular underpinnings underlying immunomodulatory properties of HK M. obuense are still largely undefined. To fill this void, we sought to perform immunophenotyping, chemokine/cytokine release analysis and genome-wide characterization of monocyte-derived macrophages (MDM) in which monocytes were originally isolated from healthy donors and differentiated by HK M. obuense (Mob-MDM) relative to M-CSF (M-MDM) and GM-CSF (GM-MDM). Immunophenotyping and cytokine release analysis revealed a downregulated surface expression of CD36, a decreased spontaneous release of CCL2 and an increased spontaneous secretion of CCL5, CXCL8/IL-8, IL-6 and TNF- in Mob-MDM relative to M-MDM and GM-MDM. Analysis of cytostatic activity revealed that Mob-MDM exhibited similar growth inhibitory effects on immortalized and malignant epithelial cells compared with GM-MDM but at an elevated rate relative to M-MDM. To understand global cues in Mob-MDM, we performed comparative RNA-sequencing (RNA-Seq) analysis of Mob-MDM relative to GM-MDM and M-MDM (n=4 donors). Clustering analysis revealed expression profiles (n = 256) that were significantly modulated in Mob-MDM versus both M-MDM and GM-MDM including, among others, chemokines/cytokines and their receptors, enzymes and transcriptions factors. Topological functional analysis of these profiles revealed pathways and gene sets linked to Mob-MDM phenotype including nitric oxide production, acute phase response signaling and microbe recognition pathways as well as signaling cues mediated by the pro-inflammatory cytokine, interferon-gamma (IFNG), and the intracellular pattern recognition receptor, nucleotide-binding oligomerization domain-containing protein 2 (NOD2). Taken together, our study highlights molecular immune phenotypes and global signaling cues in Mob-MDM and thus may underlie immunomodulatory properties of HK M. obuense. Such properties could be of valuable use for the immunotherapy as well as the adoptive cell therapy approaches in cancer.